Intervalos de Referência Hematológicos do Morcego Tadarida brasiliensis (Molossidae, Chiroptera) no sul do Brasil - Menezes, Paulo Quadros de (2020)
Hematological and biochemical analyzes are important tools in human and animal medicine, supporting the diagnosis of diseases and treatment decisions. These analyzes also have applications in decisions on the management and conservation of wild species. Reference intervals (RI) are ranges of values from healthy individuals and considered normal for a population or species, which are used to interpret the results of hematological and biochemical analyzes. The establishment of RI for wild animals involves a series of methodological difficulties and work with bat species is rare. The objective of the present study is to establish for the first time 12 hematological Reference Intervals of a species of Molossidae, Tadarida brasiliensis, an insectivorous bat with wide geographic distribution, abundant and synanthropic. The study was carried out with 139 healthy adult individuals, including males and females, captured in two shelters in buildings for 12 months in the south of Rio Grande do Sul, in the extreme south of Brazil. The results indicate that T. brasiliensis presents a wide variation in red blood cell count, hemoglobin concentration and hematocrit, with lower values of the lower limits of the RI when compared to species from other families. The IRs obtained for VCM and CHCM follow a different pattern with little variation and low values when compared to other families. The IR for platelet count in T. brasiliensis was broad and with very high upper limit values. The IR for total proteins was little variable and low. Tadarida brasiliensis presents leukocyte cells composed of segmented neutrophils, lymphocytes, eosinophils and monocytes. The RI for total leukocyte, neutrophil, lymphocyte and monocyte count were low and little variable and the eosinophil count is high and variable. The ratio between segmented neutrophils and lymphocytes is proportional in the species. Eosinophils were detected in 75 (88.2%) of the 85 individuals analyzed and monocytes were detected in 16 (18.6%) individuals of the 86 analyzed. The establishment of IR for T. brasiliensis represents an initial step in the hematological study of Molossidae species, with potential for early detection of diseases, including zoonoses, and in management and conservation.